Amyotrophic lateral sclerosis and cancer – a register-based study in Sweden - Fang, Fang (Amyotroph Lateral Scler Frontotemporal Degener, 2013)
OBJECTIVE: Comorbidity of cancer with ALS has been studied previously. Detailed description of the temporal relationship between cancer and ALS is however lacking. METHODS: We conducted a nested case-control study of ALS in Sweden during 1987–2009, including 5481 cases of ALS identified from the Swedish Patient Register and 27,405 controls randomly selected from the general Swedish population. Odds ratios (ORs) for association of ALS with previous cancer diagnosis and incidence rate ratios (IRRs) of cancer after diagnosis were calculated to compare ALS patients to ALS-free individuals. RESULTS: Overall, a previous cancer diagnosis was not associated with subsequent risk of ALS (OR 1.00; 95% CI 0.91–1.10). No overall association was observed for any specific cancer type. An increased risk of ALS was observed during the first year after cancer diagnosis (OR 1.50; 95% CI 1.17–1.92). In contrast, a lower risk of cancer was observed in ALS patients after diagnosis compared to ALS-free individuals (IRR 0.84; 95% CI 0.69–1.02). The risk reduction was seen primarily two or more years after ALS diagnosis (IRR 0.64; 95% CI 0.45–0.88). CONCLUSIONS: Our results provide no evidence for comorbidity of cancer and ALS overall. Surveillance biases seem the most likely explanation for the limited associations detected.